2011
DOI: 10.1017/s1041610211002389
|View full text |Cite
|
Sign up to set email alerts
|

Could cholinesterase inhibitors be harmful over the long term?

Abstract: Given the rather modest clinical effects of cholinesterase inhibitors, an important question is: For how long should they be prescribed? The clinical trials that supported marketing of the drugs were only 3–6 months in duration. A couple of 12-month, placebo-controlled donepezil trials showed some advantage for Mini-Mental State Examination (MMSE) scores and maintaining a level of activities of daily living (ADL) function during that interval (Mohs et al., 2001; Winblad et al., 2001). The controversial AD2000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
0
7
0
1
Order By: Relevance
“…They also contain the potential for substantial risk that erroneous conclusions about both efficacy and tolerability could be made. [16][17][18][19][20] A manual search of included references was completed to supplement the database search.…”
Section: Methodsmentioning
confidence: 99%
“…They also contain the potential for substantial risk that erroneous conclusions about both efficacy and tolerability could be made. [16][17][18][19][20] A manual search of included references was completed to supplement the database search.…”
Section: Methodsmentioning
confidence: 99%
“…Cholinesterase inhibitors have consistently shown a symptomatic benefit in mild to severe dementia due to AD in randomized, double-blind, placebo-controlled trials (Birks, 2006). It has, however, been questioned whether long-term treatment with ChEIs could be harmful (Schneider, 2012). A recent metaanalysis found that AD patients treated with symptomatic treatments had a faster rate of cognitive decline (Kennedy et al, 2018).…”
Section: Symptomatic Medications For Alzheimer Disease and Cognitive mentioning
confidence: 99%
“…Even worse, Sona et al (2012) showed, through a follow-up of 18 months, that the long-term use of cholinesterase inhibitors was associated with a higher risk of rapid cognitive decline in people with a diagnosis of AD. Of note is that cholinesterase inhibitors have also been associated with other adverse effects, in particular, a higher rate of bradycardia, syncope, insertion of a pacemaker, and hip fracture (Schneider, 2012). In addition, a meta-analysis and systematic review conducted by Tricco et al (2013) showed that cholinesterase inhibitors and memantine did not improve cognitive abilities or functional status of individuals with MCI.…”
Section: Another Approach To Alzheimer's Disease and Another Researchmentioning
confidence: 99%